NILAI DIDAKTIS UPACARA PACARUAN SASIH KAENEM DI PURA PASEK NGUKUHIN, DESA PAKRAMAN TONJA, KOTA DENPASAR - Ni Made Sukrawati (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
The Pacaruan Sasih Kaenem ceremony in Pura Pasek Ngukuhin, Desa Pakraman Tonja, Denpasar is interesting to be elaborated since it is related to a number of myths and always accompanied by procession of taking down (nedunang) tapakan Barong and Rangda. This local tradition still persists and continues till today because of its didactic values. The ceremonial procession, the didactic value, and the transmission of the didactic value to the Hindus become the main focus of this article. The ceremony of Pacaruan Sasih Kaenem can be divided into three stages, namely the initial procession, the core, and the end. The didactic value found in the ceremony includes the value of education tattwa, susila, and acara. The transmission of the didactic value is done through three methodology, namely religiousideology, myth, and social system.